2006
DOI: 10.1002/dvg.20230
|View full text |Cite
|
Sign up to set email alerts
|

Maternal methyl supplements increase offspring DNA methylation at Axin fused

Abstract: Transient environmental exposures during mammalian development can permanently alter gene expression and metabolism by influencing the establishment of epigenetic gene regulatory mechanisms. The genomic characteristics that confer such epigenetic plasticity upon specific loci, however, have not been characterized. Methyl donor supplementation of female mice before and during pregnancy permanently increases DNA methylation at the viable yellow agouti (A(vy)) metastable epiallele in the offspring. The current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
319
1
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 454 publications
(333 citation statements)
references
References 24 publications
9
319
1
4
Order By: Relevance
“…Interestingly though, the DNA methylation status, gene expression and phenotype related to both these gene loci can be modified by dietary methyl donor supplementation in early development. 39,40 There is a recent report that nutritional supplementation can lead to germline epigenetic modification in agoutimouse model. 35 The three reports of TGRs in humans show some concordance in outcome in the descendants.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly though, the DNA methylation status, gene expression and phenotype related to both these gene loci can be modified by dietary methyl donor supplementation in early development. 39,40 There is a recent report that nutritional supplementation can lead to germline epigenetic modification in agoutimouse model. 35 The three reports of TGRs in humans show some concordance in outcome in the descendants.…”
Section: Discussionmentioning
confidence: 99%
“…This concept of a retro-element triggered ME was confirmed in the murine Axin Fu mutation, at which interindividual variation in methylation is associated with tail kinking (Rakyan et al, 2002). It was shown that methylation at MEs occurs stochastically but can in part be modified by maternal intake of nutrients related to one-carbon metabolism (Waterland et al, 2006;Waterland and Jirtle, 2003). In addition the methylation state can in part be transmitted via a parental germline, either maternal (A vy ) (Morgan et al, 1999) or paternal (Axin Fu ) (Rakyan et al, 2003).…”
Section: Introductionmentioning
confidence: 90%
“…However, the extent to which the modification is perpetuated is by simple persistence of the environmental factors that bring about the epigenetic modification; that is, in each generation individuals are exposed to the same conditions. For example, if the diet [112,29] or environmental toxicant such as lead continues to be present in the environment, then the epigenetic modification will be manifest each generation. This type of epigenetic modification lends itself to relatively straightforward therapeutic venues such as providing methyl donors to the diet [112] or removing the environmental toxicant (smoke or lead).…”
Section: Context-dependent Epigenetic Modificationmentioning
confidence: 99%